On the Homomorphisms of the Lie Groups and - Fatma Özdemir; Hasan Özekes (Abstract and Applied Analysis)
We first construct all the homomorphisms from the Heisenberg group to the 3-sphere. Also, defining a topology on these homomorphisms, we regard the set of these homomorphisms as a topological space. Next, using the kernels of homomorphisms, we define an equivalence relation on this topological space. We finally show that the quotient space is a topological group which is isomorphic to .